2017
DOI: 10.1016/j.dcn.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Interoception and psychopathology: A developmental neuroscience perspective

Abstract: Interoception refers to the perception of the physiological condition of the body, including hunger, temperature, and heart rate. There is a growing appreciation that interoception is integral to higher-order cognition. Indeed, existing research indicates an association between low interoceptive sensitivity and alexithymia (a difficulty identifying one's own emotion), underscoring the link between bodily and emotional awareness. Despite this appreciation, the developmental trajectory of interoception across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
224
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 313 publications
(247 citation statements)
references
References 208 publications
21
224
0
2
Order By: Relevance
“…One of the limitations of the current study is that its conclusions are valid for healthy individuals only; atypical interoception may lead to issues in psychological development and represent a general susceptibility to psychopathology (Murphy, Brewer, Catmur, & Bird, ). Extremely low and high levels of interoceptive accuracy with respect to one single modality might also have modality‐specific pathological consequences.…”
Section: Discussionmentioning
confidence: 95%
“…One of the limitations of the current study is that its conclusions are valid for healthy individuals only; atypical interoception may lead to issues in psychological development and represent a general susceptibility to psychopathology (Murphy, Brewer, Catmur, & Bird, ). Extremely low and high levels of interoceptive accuracy with respect to one single modality might also have modality‐specific pathological consequences.…”
Section: Discussionmentioning
confidence: 95%
“…Although this associative learning process has been proposed to be integral for development in infancy, any period in which substantial physical change occurs may require (re)learning and contextualisation of new or altered interoceptive sensations (Murphy et al, 2017).…”
Section: Whilst Systematic Investigation Of the Impact Of Physical Anmentioning
confidence: 99%
“…Taken together, these studies may indicate that increased awareness of present experience, particularly awareness of bodily sensations, may be one mechanism by which alexithymia is reduced. Alexithymia (awareness of emotional experience) has been found to be strongly related to interoception (awareness of bodily experience)40 and improvement in alexithymia symptoms has been associated with increased heartbeat perception accuracy 35. Furthermore, Santarnecchi et al 37 reported a significant correlation between the decrease in alexithymia and an increase in right insula thickness, an area of the brain, which is involved in both emotional and bodily awareness 41.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%